Avaliação da prevalência e suscetibilidade antifúngica de candida isoladas da cavidade bucal de pacientes infanto-juvenis com leucemia linfocítica aguda - Monteiro, Larissa Cavalcanti (2015)
Introduction: Acute lymphocytic leukemia (ALL) is the most common malignancy in childreen accounting for 75% of all diagnosed leukemias and being 25% of all malignancies in childhood. There are few studies that deal directly with the understanding of the clinical profile and other variables associated with oral Candida colonization in pediatric patients with ALL, especially in developing countries. Objective: The aim of this study was to evaluate antifungal resistance and Candida colonization in oral cavity of infant juvenile ALL patients. Material and Methods: This was a cross sectioned design, controlled, with dual observational and descriptive characteristics. To carry out this study, two groups were formed: a ALL group with 40 patients diagnosed with ALL and a control group, formed by 40 healthy individuals matched by age and gender. All these individuals were clinically evaluated and submitted to salivary collection with sterile swab. The saliva was seeded onto CHROMagar CandidaTM, incubed for 48hs at 37oC, and the obtained colony formation unities (CFU) were counted and presumptively identified. Variable data of the participants were collected and stored in individual files. The found species was submitted to microdilution for Nystatin and Amphotericin B, widely used treating candidosis, to establish their susceptibility/resistance. Results: Of 40 patients evaluated in case group, 13 (32.5%) were positive to Candida and only 1 (2.5%) was positive in control group (p<0.001). Candida albicans was the most prevalent strain (87.5%). All patients who had 10³ CFU/mL counts were on induction phase of chemotherapy. Of analysed variables, only mucositis was directly associated with Candida positiveness (p=0.017) on ALL group. Five out 14 strains of C. albicans (35.7%) were resistant to Nystatin and all species were not susceptible to Ampothericin B. Conclusion: Candida colonization was associated with ALL probably vinculated to mucositis events being the higher counts found on induction phase of chemotherapy. C. albicans was the prevalent strain and resistance and lack of susceptibility to Nystatin and Amphotericin B was found.